FAKTOR-FAKTOR YANG MEMPENGARUHI KECURANGAN PADA PENGELOLAAN DANA DESA DI KECAMATAN X - Sabilla Tian Safitri; Junaidi Junaidi; Hariri Hariri (e_Jurnal Ilmiah Riset Akuntansi, 2022)
According to the assessment of the trend of cracking down on corruption cases according to the Indonesian Corruption Watch (ICW), village fund fraud every year continues to exist. With losses reaching billions of rupiah. This study aims to determine the influence of the level of competence of village officials, religiosity, morality, effectiveness of internal control and compensation suitability in the occurrence of fraud in village fund management in sub-district X. This type of research is a quantitative research of direct survey methods. The questionnaire used a likert scale with a value of 1-5. Hypothesis testing uses multiple linear regression analysis with SPSS applications. The population and sample were village fund management officers in District X with a total of 56 respondents. The test results showed that simultaneously the level of competence of village officials, religiosity, morality, effectiveness of internal control and the suitability of compensation F value calculated 125.518 > F table 2.40. Partially, the level of competence of village officials, religiosity, morality, effectiveness of internal control does not affect fraud in the management of village funds in the sub-district. Meanwhile, partially the suitability of compensation affects fraud in village fund management in District X. Research is expected to be an evaluation so that village officials evaluate themselves so that village fund management is safe from fraud and does not harm the community or themselves.  Keywords: fraud in village fund management, level of competence, religiosity, morality, effectiveness of internal control, suitability of compensation.